2005
DOI: 10.1080/j.1440-1614.2005.01714.x
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the Onset of Psychosis: The Comprehensive Assessment of At-Risk Mental States

Abstract: In these preliminary investigations, the CAARMS displayed good to excellent concurrent, discriminant and predictive validity and excellent inter-rater reliability. The CAARMS instrument provides a useful platform for monitoring subthreshold psychotic symptoms for worsening into full-threshold psychotic disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
1,402
2
15

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,793 publications
(1,474 citation statements)
references
References 16 publications
13
1,402
2
15
Order By: Relevance
“…The catchment area includes the boroughs served by South London and Maudsley NHS Foundation Trust. UHR individuals were assessed by the OASIS service using the Comprehensive Assessment of AtRisk Mental States (CAARMS) assessment tool (Yung et al, 2005) Conferral of an at-risk status was established by two experienced clinicians and a consensus meeting of the OASIS clinical team.…”
Section: Participantsmentioning
confidence: 99%
“…The catchment area includes the boroughs served by South London and Maudsley NHS Foundation Trust. UHR individuals were assessed by the OASIS service using the Comprehensive Assessment of AtRisk Mental States (CAARMS) assessment tool (Yung et al, 2005) Conferral of an at-risk status was established by two experienced clinicians and a consensus meeting of the OASIS clinical team.…”
Section: Participantsmentioning
confidence: 99%
“…Scheduled Interview for Prodromal Symptoms/Scale of Prodromal Symptoms (SIPS/ SOPS) Miller et al 2003], in an attempt to better predict the onset of psychosis. At PACE, the Comprehensive Assessment of At-Risk Mental States (CAARMS; Yung et al 2005) is used to rate the UHR status of young people at the age of peak risk for psychosis based on the criteria of: (1) attenuated psychotic symptoms; (2) brief limited intermittent psychotic symptoms (BLIPS); and/or (3) trait vulnerability for psychotic illness (schizotypal personality disorder or a history of psychosis in a first-degree relative), and deterioration in functioning or chronic low functioning.…”
mentioning
confidence: 99%
“…The past twenty years have seen increasingly rapid advances in the field of early intervention [1][2][3] ; not only due to the relevance of the issue but also because studies showed its positive impact and cost-effectiveness 4,5 . Early intervention aims to investigate early stages of psychosis also known as prodromal phase.…”
Section: Introductionmentioning
confidence: 99%
“…UHR are individuals at risk to develop psychosis who present the following symptoms at least two weeks most of the days: suspiciousness, perceptual distortions, poor or decline functioning, social withdrawal, hallucinations, disorganized thinking/speech, ideas of reference, depression, anxiety, sleep disturbance, difficulties in concentration that might indicate a risk of conversion to psychosis 1,3,6 and cognitive impairments 7,8 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation